Fluorodeoxyglucose positron emission tomography scans in patients with alcohol use disorder. (10th May 2022) - Bralet, Marie‐Cécile; Mitelman, Serge A.; Goodman, Chelain R.; Lincoln, Samantha; Hazlett, Erin A.; Buchsbaum, Monte S.
Abstract: Background: Diminished uptake of fluorodeoxyglucose (FDG) has been observed in patients with alcohol use disorder (AUD) but little statistical contrast of the regional brain deficits has been undertaken. This study examined prefrontal cortex inter‐regional Brodmann area differences to delineate patterns associated with behavioral, neurotransmitter, and general toxicity hypotheses of cerebral involvement in AUD. Methods: We obtained data from FDG positron emission tomography (PET) and anatomical magnetic resonance imaging (MRI) for 87 patients with AUD and 41 age‐ and sex‐matched healthy volunteers. Patients were alcohol dependent and had negative breathalyzer tests at the time of imaging. They were assessed with the Beck Depression Inventory, Alcohol Urge Questionnaire, Obsessive Compulsive Drinking Scale, Spielberger State/Trait Anxiety Scale, Buss–Durkee Hostility Inventory, and the Drinker Inventory of Consequences (DrInC). PET images were co‐registered to MRI and both voxel × voxel statistical mapping and stereotaxic regions of interest were obtained. Results: Compared with healthy volunteers, patients with AUD had lower relative metabolic rates in the frontal, temporal, and parietal lobes, localizable most prominently to the dorsolateral and nearly all orbital prefrontal cortex, superior temporal gyrus, and inferior parietal lobule. In contrast, metabolic rates in the medial orbitofrontal and anterior cingulate cortex, and the subcortical structures (thalamus, cerebellum, ventral striatum, and the dorsal raphe nucleus) in patients were significantly greater. The severity of alcohol‐related consequences as assessed by the DrInC scale was most highly associated with lower metabolism in the caudate, dorsolateral prefrontal, frontopolar, and anteroposterior cingulate cortex. Conclusions: Despite widespread metabolic abnormalities, decreases in AUD were most marked in frontal executive areas, consistent with diminished impulse control, and increases were most prominent in the striatum and cingulate areas, consistent with a suppressed reward system. Abstract : We obtained FDG positron emission tomography on 87 patients with Alcohol Use Disorder (AUD) and 41 age‐and sex‐matched healthy volunteers. Patients with AUD had reduced relative metabolic rates in the dorsolateral frontal cortex and elevated rates in the medial orbitofrontal, cingulate cortex, and subcortical structures (thalamus, ventral striatum). Decreases in AUD were most marked in frontal executive areas, consistent with diminished impulse control, and increases were most prominent in the striatum and cingulate areas, consistent with a suppressed reward system.